2014
DOI: 10.1111/ene.12579
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid immunological biomarkers associated with axonal damage in multiple sclerosis

Abstract: High CSF NFL levels are associated with elevated CSF lymphocyte cell counts and intrathecal synthesis of IgM against lipids. These findings support a role for OCMB in the axonal damage of MS offering a rationale for the association of these antibodies with disability and brain atrophy progression in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 37 publications
10
39
0
Order By: Relevance
“…WLG has also been reported as a predictive tool for cognitive impairment in patients with clinically isolated syndrome . We demonstrated an inverse association between WLG and NF‐L levels, with NF‐L being a predictive biomarker of inflammation in early stages of MS when patients showed moderate disability . These data are consistent with previous reports showing association between other neuroinflammation‐related markers and impairment in basic attention tasks in patients with MS .…”
Section: Discussionsupporting
confidence: 92%
“…WLG has also been reported as a predictive tool for cognitive impairment in patients with clinically isolated syndrome . We demonstrated an inverse association between WLG and NF‐L levels, with NF‐L being a predictive biomarker of inflammation in early stages of MS when patients showed moderate disability . These data are consistent with previous reports showing association between other neuroinflammation‐related markers and impairment in basic attention tasks in patients with MS .…”
Section: Discussionsupporting
confidence: 92%
“…A similar significant association was found between sNfL and presence of spinal GE lesions and was most pronounced when GE lesions were present in both brain and spinal cord. Several studies have shown associations between CSF NfL and brain T2 and GE lesions 7, 12, 45. We have also previously shown weak associations between sNfL (as measured by the ECL assay) and brain T2 and GE lesions in CIS patients18 and in a small cohort of RRMS patients (n = 29) 19.…”
Section: Discussionsupporting
confidence: 53%
“…NfL levels are increased in the cerebrospinal fluid (CSF) of MS patients as well as in degenerative and traumatic neurological diseases (eg, dementia, amyotrophic lateral sclerosis, and spinal cord injury) 4, 5, 6, 7, 8, 9. CSF NfL levels are further increased during relapses and are positively associated with magnetic resonance imaging (MRI) lesion load and disability scores in MS 10, 11, 12.…”
mentioning
confidence: 99%
“…Multiple sclerosis (MS) is a field of neurology that has undergone tremendous advances within only the last 15 years . The advent of immunological therapies has transformed outcome for patients with relapsing−remitting disease, although the effect on chronic progressive disease is less certain.…”
mentioning
confidence: 99%